2020
DOI: 10.3389/fonc.2019.01461
|View full text |Cite
|
Sign up to set email alerts
|

Linking NRP2 With EMT and Chemoradioresistance in Bladder Cancer

Abstract: Neuropilin-2 (NRP2) is a prognostic indicator for reduced survival in bladder cancer (BCa) patients. Together with its major ligand, vascular endothelial growth factor (VEGF)-C, NRP2 expression is a predictive factor for treatment outcome in response to radiochemotherapy in BCa patients who underwent transurethral resection. Therefore, we investigated the benefit of combining cisplatin-based chemotherapy with irradiation treatment in the BCa cell line RT112 exhibiting or lacking endogenous NRP2 expression in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Human gene NRP2 produces neuropilin 2, the downregulation of which improves survival after radiochemotherapy [ 83 ], thereby raising reproductive potential consistently with wolf orthologous gene downregulation in microevolution [ 28 ] ( Table 4 ). Conversely, an NRP2 excess causes post-traumatic vascular neointimal hyperplasia [ 84 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Human gene NRP2 produces neuropilin 2, the downregulation of which improves survival after radiochemotherapy [ 83 ], thereby raising reproductive potential consistently with wolf orthologous gene downregulation in microevolution [ 28 ] ( Table 4 ). Conversely, an NRP2 excess causes post-traumatic vascular neointimal hyperplasia [ 84 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…A multivariate Cox regression analysis also revealed NRP2 as an independent prognostic factor for OS in this cohort [ 12 ]. The role of NRP2 in the therapy response was corroborated in vitro where we showed that NRP2 downregulation sensitized BLCA cells to radiochemotherapy [ 31 ]. However, the prognostic value of NRP2 may be limited to MIBC.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, our current study investigated NRP2 gene expression while Keck et al investigated NRP2 protein levels [ 12 ]. In light of our reports indicating post-transcriptional regulation that may influence NRP2 protein levels [ 31 ], a direct comparison of immunohistochemical NRP2 staining with mRNA expression should be performed in the future to clarify this issue. However, our current study was particularly focused on messenger expression as we were interested in the potential involvement of NRP2 isoforms/transcript variants in UBC but no isoform-specific antibodies are commercially available yet.…”
Section: Discussionmentioning
confidence: 99%
“…EMT changes the polarity of the cells, deconstructs the cell connections, adjusts the motility of cells, and modifies the cytoskeleton, changes that together may contribute to the promotion of tumor cell metastasis (14). To evaluate whether EMT occurs requires the detection of relevant molecular markers such as E-cadherin, N-cadherin, and vimentin (15). Hence, we further examined the role of EMT-related molecular markers in the context of RAD18-mediated invasion and migration of CRC cells.…”
Section: Rad18 Promotes Colorectal Cancer Metastasis By Activating Thmentioning
confidence: 99%